The Quest to Model Chronic Traumatic Encephalopathy: A Multiple Model and Injury Paradigm Experience - Turner, Ryan C.; Lucke-Wold, Brandon P.; Logsdon, Aric F.; Robson, Matthew J.; Dashnaw, Matthew L.; Huang, Jason H.; Smith, Kelly E.; Huber, Jason D.; Rosen, Charles L.; Petraglia, Anthony L. (Frontiers in Neurology, 2015)
Chronic neurodegeneration following a history of neurotrauma is frequently associated with neuropsychiatric and cognitive symptoms. In order to enhance understanding about the underlying pathophysiology linking neurotrauma to neurodegeneration, a multi-model pre-clinical approach must be established to account for the different injury paradigms and pathophysiologic mechanisms. We investigated the development of tau pathology and behavioral changes using a multi-model and multi-institutional approach, comparing the pre-clinical results to tauopathy patterns seen in post-mortem human samples from athletes diagnosed with chronic traumatic encephalopathy (CTE). We utilized a scaled and validated blast-induced traumatic brain injury model in rats and a modified pneumatic closed-head impact model in mice. Tau hyperphosphorylation was evaluated by western blot and immunohistochemistry. Elevated plus maze and Morris water maze were employed to measure impulsive-like behavior and cognitive deficits respectively. Animals exposed to single blast (~50 PSI reflected peak overpressure) exhibited elevated AT8 immunoreactivity in the contralateral hippocampus at 1 month compared to controls (q = 3.96, p < 0.05). Animals exposed to repeat blast (6 blasts over 2 weeks) had increased AT8 (q = 8.12, p < 0.001) and AT270 (q = 4.03, p < 0.05) in the contralateral hippocampus at 1 month post-injury compared to controls. In the modified controlled closed-head impact mouse model, no significant difference in AT8 was seen at 7 days, however a significant elevation was detected at 1 month following injury in the ipsilateral hippocampus compared to control (q = 4.34, p < 0.05). Elevated plus maze data revealed that rats exposed to single blast (q = 3.53, p < 0.05) and repeat blast (q = 4.21, p < 0.05) spent more time in seconds exploring the open arms compared to controls. Morris water maze testing revealed a significant difference between groups in acquisition times on days 22-27. During the probe trial, single blast (t = 6.44, p < 0.05) and repeat blast (t = 8.00, p < 0.05) rats spent less time in seconds exploring where the platform had been located compared to controls. This study provides a multi-model example of replicating tau and behavioral changes in animals characteristic of a CTE phenotype.